2017
DOI: 10.1210/js.2017-00262
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Sugar-Sweetened Beverage Consumption and the Onset of Cardiometabolic Diseases: Cause for Concern?

Abstract: The incidence of noncommunicable diseases is on the rise and poses a major threat to global public health. This is in parallel to a steady increase in worldwide intake of sugar-sweetened beverages (SSBs) among all age groups. As several studies demonstrated a controversial relationship between SSB consumption and the metabolic syndrome (MetS), this mini-review focuses on links between its intake and (1) MetS, (2) prediabetes/type 2 diabetes mellitus (T2DM), and (3) hypertension. A detailed search for clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 65 publications
0
29
1
3
Order By: Relevance
“…The South African Adult PURE cohort study showed an association between higher consumption of added sugars and sucrose-sweetened beverages with increased non-communicable disease risk factors [69]. The role of SSBs in driving obesity and its associated complications has been supported in a recent review [70]. A lack of association between bread intake and BMI observed in this study is not congruent with other studies [47,71].…”
Section: Discussioncontrasting
confidence: 71%
“…The South African Adult PURE cohort study showed an association between higher consumption of added sugars and sucrose-sweetened beverages with increased non-communicable disease risk factors [69]. The role of SSBs in driving obesity and its associated complications has been supported in a recent review [70]. A lack of association between bread intake and BMI observed in this study is not congruent with other studies [47,71].…”
Section: Discussioncontrasting
confidence: 71%
“…24,25 Directly targeting SSB consumption in the clinical setting may have the potential to impact the prevention of cardiometabolic disease. 26 In a rural practice with higher numbers of children, given the higher risk of obesity, identification of SSB consumption and targeted interventions may be even more imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their prevalence rapidly increased over the past few decades and they continue to rise, especially in low-and middle-income countries. Here, excess sugar-sweetened beverage (SSB) intake is emerging as a crucial mediator of such pathology [2] as it is linked with hyperglycemia, dyslipidemia, hyperinsulinemia, and weight gain [3,4]. In support, increased SSB intake is associated with suboptimal lifestyle choices (reduced physical activity, poor dietary choices) [5] and the development of insulin resistance and T2DM [6,7].…”
Section: Introductionmentioning
confidence: 99%